C.i. pigment yellow 101, method for producing the same, and coloring composition containing c.i. pigment yellow 101
By controlling the particle size and X-ray diffraction pattern peaks of C.I. Pigment Yellow 101 during diameter reduction, the method ensures the pigment retains its fluorescent color and performance, addressing the issue of color loss in smaller diameters.
Patent Information
- Application Number
- JP2023166029
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
When the diameter of C.I. Pigment Yellow 101 is reduced, it often results in a fluorescent color loss due to changes in the crystal structure, which affects its coloring performance.
A method to reduce the diameter of C.I. Pigment Yellow 101 while maintaining its fluorescent color by controlling the average particle size between 100 nm and 700 nm and optimizing the X-ray diffraction pattern peaks, specifically ensuring the second peak from the low angle side remains within the diffraction angle of 2θ=11.66° to 11.86°, and the third peak within 2θ=17.86° to 18.06°, using specific bead milling conditions.
The method achieves a C.I. Pigment Yellow 101 with a higher fluorescent color even at a smaller diameter, compared to conventional methods, by minimizing changes in the crystal structure and maintaining optimal peak positions in the X-ray diffraction pattern.
Smart Images

Figure 2025056510000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to CI Pigment Yellow 101, a method for producing the same, and a coloring composition containing CI Pigment Yellow 101. [Background technology]
[0002] Organic pigments are used in toners for electrophotographic image forming devices, and color filters for liquid crystal displays, electronic paper, and organic electroluminescence displays. In recent years, the required image quality, such as high color definition, has become more sophisticated. In response to this, organic pigments are being used with smaller particle sizes in order to improve coloring power.
[0003] For example, Patent Document 1 discloses "an insoluble azo pigment having a particle size of 30 to 150 nm and high crystallinity." [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-26930 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when the particle size of the yellow organic pigment CI Pigment Yellow 101 was reduced, the fluorescent color was sometimes lost due to the reduced particle size.
[0006] The object of the present invention is to provide CI Pigment Yellow 101, which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in a range of diffraction angles 2θ=11.66° or more or 2θ=11.86° or more, and which has a higher fluorescent color even with a smaller particle size than CI Pigment Yellow 101. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects. <1> The average particle size is 100 nm or more and 700 nm or less, In the X-ray diffraction pattern obtained by powder X-ray diffraction method, the second peak from the low angle side is present in the range of diffraction angle 2θ = 11.66 ° or more and 11.86 ° or less. CI Pigment Yellow 101. <2> having an average particle size of 150 nm or more and 500 nm or less; <1> CI Pigment Yellow 101 as described in. <3> In the X-ray diffraction pattern obtained by powder X-ray diffraction method, the third peak from the low angle side is present in the range of diffraction angle 2θ = 17.86 ° or more and 18.06 ° or less. <1> CI Pigment Yellow 101 as described in. <4> The method includes reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of 1 μm or more and 5 μm or less, using beads having a specific gravity of 2.5 or more and 6.0 or less and a bead diameter of 0.03 mm or more and 0.3 mm or less, under the condition that the peripheral speed of the stirring mechanism is 4.8 m / s or more and 14.4 m / s or less, <1> 2. A method for producing CI Pigment Yellow 101 according to claim 1. <5> <1> ~ <3> A coloring composition comprising CI Pigment Yellow 101 according to any one of claims 1 to 5. <6> The coloring composition is a toner for developing an electrostatic image. <5> The coloring composition according to claim 1. Effect of the Invention
[0008] <1> According to the present invention, there is provided CI Pigment Yellow 101, which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in a range of diffraction angles 2θ=11.66° or more or 2θ=11.86° or more, and which has a higher fluorescent color even though it has a smaller particle size than CI Pigment Yellow 101.
[0009] <2> According to the present invention, CI Pigment Yellow 101 is provided that has a high fluorescent color even with a small diameter, compared to when the average particle size is 100 nm or more but less than 150 nm, or more than 500 nm but not more than 700 nm.
[0010] <3> According to the present invention, there is provided CI Pigment Yellow 101 which has a high fluorescent color even with a small diameter, compared with a case in which, in an X-ray diffraction pattern obtained by powder X-ray diffraction, the second peak from the low angle side is in the range of diffraction angles 2θ=11.66° or more and 11.86° or less, and, in an X-ray diffraction pattern obtained by powder X-ray diffraction, the third peak from the low angle side is in the range of diffraction angles 2θ=less than 17.86° or more than 2θ=18.06°.
[0011] <4> According to the present invention, there is provided a method for producing CI Pigment Yellow 101 having a high fluorescent color even with a small diameter, as compared with a method for producing CI Pigment Yellow 101 that includes reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of 1 μm or more and 5 μm or less under conditions in which beads having a specific gravity of less than 2.5 or more than 6.0, or a bead diameter of less than 0.03 mm or more than 0.3 mm are used, or the peripheral speed of a stirring mechanism is less than 4.8 m / s or more than 14.4 m / s.
[0012] <5> According to the present invention, there is provided a coloring composition containing CI Pigment Yellow 101, which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in a range of diffraction angles 2θ=11.66° or more or 2θ=11.86°, and has a high fluorescent color even with a small particle size compared to when CI Pigment Yellow 101 is used.
[0013] <6> According to the invention, there is provided a coloring composition, which is a toner for developing electrostatic images, containing CI Pigment Yellow 101, which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in a range of diffraction angles 2θ=11.66° or more or 2θ=11.86°, and has a high fluorescent color even with a small particle size compared to when CI Pigment Yellow 101 is used. [Brief description of the drawings]
[0014] [Figure 1] Fig. 1 is a schematic diagram showing an example of an X-ray diffraction pattern obtained by powder X-ray diffraction of CI Pigment Yellow 101 of this embodiment. Fig. 1(A) is a schematic diagram showing an example of an X-ray diffraction pattern obtained by powder X-ray diffraction of CI Pigment Yellow 101 before size reduction. Fig. 1(B) is a schematic diagram showing an example of an X-ray diffraction pattern obtained by powder X-ray diffraction of CI Pigment Yellow 101 after size reduction (Example). Fig. 1(C) is a schematic diagram showing an example of an X-ray diffraction pattern obtained by powder X-ray diffraction of CI Pigment Yellow 101 after size reduction (Comparative Example). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the present invention.
[0016] In this embodiment, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present embodiment, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described in the present embodiment. In addition, in the numerical ranges described in the present embodiment, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0017] In this embodiment, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.
[0018] In the present embodiment, when the embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.
[0019] In this embodiment, each component may contain a plurality of corresponding substances. In this embodiment, when the amount of each component in the composition is mentioned, if a plurality of substances corresponding to each component are present in the composition, the amount means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0020] In the present embodiment, the term "(meth)acrylic" means either "acrylic" or "methacrylic".
[0021] In this embodiment, the term "fluorescent color" refers to the color of light having a wavelength of 510 nm or more and 530 nm or less (green).
[0022] <C.I.ピグメントイエロー101> The CI Pigment Yellow 101 of this embodiment is The average particle size is 100 nm or more and 700 nm or less, In the X-ray diffraction pattern obtained by powder X-ray diffraction method, the second peak from the low angle side is present in the range of diffraction angle 2θ = 11.66° or more and 11.86° or less, which is CI Pigment Yellow 101.
[0023] The CI Pigment Yellow 101 of this embodiment has the above-mentioned structure, and therefore has a high fluorescent color even with a small diameter. The reason for this is presumed to be as follows.
[0024] CI Pigment Yellow 101 is a colorant that exhibits fluorescent colors. On the other hand, commercially available CI Pigment Yellow 101 has particles of about 3 μm, and when used in colored compositions such as toners, the particle size is reduced to improve inclusion in the composition and coloring properties of the composition.
[0025] Here, the mechanochemical method is widely used as a method for reducing the diameter of organic pigments. However, when the diameter of CI Pigment Yellow 101 is reduced by the above-mentioned method, the fluorescent color may decrease. Depending on the size reduction method or size reduction conditions, the mechanochemical method may impart a large mechanical energy to the organic pigment during size reduction, which may cause lattice defects, lattice distortion, crystal system transition, and amorphization in the crystal structure of the organic pigment. Therefore, when CI Pigment Yellow 101 is reduced in size, it is considered that the fluorescent color decreases due to the change in the crystal structure. The change in the crystal structure can be confirmed by the change in the peak of the X-ray diffraction pattern obtained by the powder X-ray diffraction method of CI Pigment Yellow 101 after size reduction to the high angle side (or low angle side).
[0026] In contrast, in the case of CI Pigment Yellow 101 of this embodiment, even after the particle size is reduced, the second peak from the low angle side is present in the range of diffraction angle 2θ=11.66° to 11.86° in the X-ray diffraction pattern obtained by powder X-ray diffraction method (see FIG. 1(B)). This indicates that the peak of the X-ray diffraction pattern obtained by powder X-ray diffraction method in CI Pigment Yellow 101 after the particle size reduction is less shifted to the high angle side (or low angle side) than before the particle size reduction. In other words, it is presumed that the change in the crystal structure of CI Pigment Yellow 101 after the particle size reduction is less than before the particle size reduction, and the decrease in the fluorescent color is suppressed.
[0027] From the above, it is presumed that CI Pigment Yellow 101 of this embodiment has a high fluorescent color even with a small diameter.
[0028] Hereinafter, the CI Pigment Yellow 101 of this embodiment will be described in detail.
[0029] <C.I.ピグメントイエロー101> The CI Pigment Yellow 101 of this embodiment is 1,1'-[azinobismethylidyne]bis[2-naphthol]. "CI" is an abbreviation for "Colour Index".
[0030] The CI Pigment Yellow 101 of this embodiment has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in the range of diffraction angle 2θ = 11.66° or more and 11.86° or less.
[0031] The CI Pigment Yellow 101 of this embodiment has an average particle size of 100 nm or more and 700 nm or less, and therefore has a small diameter. The small diameter of the particles of CI Pigment Yellow 101 increases the specific surface area, making it easier to absorb light and easier to improve coloring power. On the other hand, from the viewpoint of preventing re-aggregation of small-sized CI Pigment Yellow 101 particles (primary particles) while maintaining the desired coloring power and imparting high fluorescent color, the average particle size of CI Pigment Yellow 101 is preferably 150 nm or more and 500 nm or less, more preferably 200 nm or more and 400 nm or less, and even more preferably 250 nm or more and 300 nm or less.
[0032] In addition, in the X-ray diffraction pattern obtained by powder X-ray diffraction method, the CI Pigment Yellow 101 of this embodiment has a second peak from the low angle side in the range of diffraction angle 2θ=11.66° to 11.86°. Since the second peak from the low angle side does not change significantly to the high angle side (or low angle side) and exists in the above range, the CI Pigment Yellow 101 has less change in crystal structure after the diameter reduction compared to before the diameter reduction. Therefore, the CI Pigment Yellow 101 of this embodiment has a high fluorescent color even at a small diameter.
[0033] In the X-ray diffraction pattern of CI Pigment Yellow 101 of this embodiment obtained by powder X-ray diffraction method, the third peak from the low angle side is preferably present in the range of diffraction angle 2θ=17.86° to 18.06°. When the third peak from the low angle side is present in the above range without a large change to the high angle side (or low angle side), the change in the crystal structure of CI Pigment Yellow 101 after the diameter reduction is smaller than that before the diameter reduction. Therefore, CI Pigment Yellow 101 of this embodiment is more likely to have a high fluorescent color even with a small diameter.
[0034] Here, in the X-ray diffraction pattern, each peak existing within the range of the diffraction angle 2θ means that the apex of the peak (the position of the highest peak intensity among the peaks existing within the range of the diffraction angle 2θ) exists within the range of the diffraction angle 2θ. In the X-ray diffraction pattern obtained by the powder X-ray diffraction method of C.I. Pigment Yellow 101 of the present embodiment, the second peak from the low-angle side and the third peak from the low-angle side respectively correspond to the peaks existing at diffraction angle 2θ = 11.66° and the peak existing at diffraction angle 2θ = 17.86° in the X-ray diffraction pattern obtained by the powder X-ray diffraction method shown in FIG. 4 of the non-patent document (Xiang Yao, et al. "Multistimuli-Responsive Luminescence of Naphthalazine Based on Aggregation-Induced Emission" ChemistryOpen Volume 4, Issue 4 p. 478-482), which are peaks slightly shifted to the high-angle side.
[0035] <Manufacturing Method of C.I. Pigment Yellow 101> The manufacturing method of C.I. Pigment Yellow 101 of the present embodiment, which has an average particle size of 100 nm or more and 700 nm or less and in the X-ray diffraction pattern obtained by the powder X-ray diffraction method, the second peak from the low-angle side exists within the range of diffraction angle 2θ = 11.66° or more and 11.86° or less, uses beads having a specific gravity of 2.5 or more and 6.0 or less and a bead diameter of 0.03 mm or more and 0.3 mm or less, and includes reducing the diameter of C.I. Pigment Yellow 101 having an average particle size of 1 μm or more and 5 μm or less under the condition that the peripheral speed of the stirring mechanism is 4.8 m / s or more and 14.4 m / s or less. As the diameter reduction method, a method using beads as media (that is, the bead mill method), and by reducing the diameter under the above conditions, C.I. Pigment Yellow 101 having a high fluorescence color even with a small diameter can be obtained.
[0036] Hereinafter, the details of the manufacturing method of C.I. Pigment Yellow 101 of the present embodiment will be described.
[0037] (Previous Step) First, CI Pigment Yellow 101 to be reduced in diameter is prepared. As the CI Pigment Yellow 101 to be reduced in diameter, a known commercially available product can be used. Commercially available products can be purchased, for example, from BASF Japan Ltd., Neelicon, and Radiant. From the viewpoint of reducing the diameter, the CI Pigment Yellow 101 to be reduced in diameter is previously adopted to have an average particle size of 1 μm or more and 5 μm or less.
[0038] The CI Pigment Yellow 101 to be reduced in diameter is preferably in the form of a slurry wetted with a liquid. Examples of the liquid for preparing the slurry include water and tetrahydrofuran, and a surfactant or dispersant may be used as necessary.
[0039] The slurry is preferably prepared so that the solid content is, for example, 5% by mass or more and 30% by mass or less relative to the total mass of the slurry, and the viscosity of the slurry is preferably, for example, 5 mPa·s or more and 500 mPa·s or less.
[0040] The slurry can be prepared by using a known stirring means such as a high-speed shear disperser or a Henschel mixer.
[0041] (Small diameter) Next, the above-prepared slurry of CI Pigment Yellow 101 is charged into the container inlet of a bead mill and the diameter of the beads is reduced.
[0042] -Bead mill operating conditions- The container of the bead mill may be of either a vertical or horizontal type.
[0043] The shape of the stirring mechanism of the bead mill can be appropriately selected from among a disk type, a pin type, a single rotor type, and the like.
[0044] The material of the beads may be appropriately selected from glass, alumina, high-purity alumina, zircon, zirconia, silicon nitride, steel, etc., so long as it satisfies a predetermined specific gravity.
[0045] The specific gravity of the beads is 2.5 or more and 6.1 or less. When the specific gravity of the beads is in the above range, excessive mechanical energy is not applied to the CI Pigment Yellow 101 during the reduction in diameter, and it is possible to obtain CI Pigment Yellow 101 having a high fluorescent color even with a small diameter. The specific gravity of the beads is preferably 3.0 or more and 5.0 or less, more preferably 3.5 or more and 4.0 or less.
[0046] The specific gravity of the beads is measured as follows. 50g of beads were placed in a 100mL measuring flask. Next, 100mL of water was measured out using a 100mL measuring cylinder. After that, the measured water was poured into the measuring flask containing the beads until it reached the marked line of the measuring flask, and the specific gravity was calculated as 50g / (volume of water remaining in the measuring cylinder) = specific gravity.
[0047] The bead diameter is 0.03 mm or more and 0.30 mm or less. By setting the bead diameter within the above range, the bead packing rate can be adjusted to a range in which the CI Pigment Yellow 101 is not subjected to excessive mechanical energy, and a CI Pigment Yellow 101 having a high fluorescent color can be obtained even with a small diameter. The bead diameter is preferably 0.07 mm or more and 0.20 mm or less, more preferably 0.10 mm or more and 0.15 mm or less.
[0048] The method for measuring the bead diameter is as follows: The beads in question are observed using an optical microscope, and images are taken. These images are then imported into an image analyzer (LUZEXIII, manufactured by Nireco Corporation) and analyzed to calculate the particle size. Specifically, the area of each bead is measured, and the equivalent circle diameter is calculated from this area value. The 50% diameter (D 50 ) is the bead diameter. Image analysis is performed on 200 arbitrarily selected beads.
[0049] The filling rate of the beads is preferably 60% by volume or more and 95% by volume or less, more preferably 70% by volume or more and 90% by volume or less, and even more preferably 75% by volume or more and 85% by volume or less, based on the volume of the bead mill container. By setting the filling rate of the beads in the above range, excessive mechanical energy is not applied to CI Pigment Yellow 101, and it is easy to obtain CI Pigment Yellow 101 having a high fluorescent color even with a small diameter.
[0050] The peripheral speed of the stirring mechanism of the bead mill is 4.8 m / s or more and 14.4 m / s or less. By setting the peripheral speed of the stirring mechanism in the above range, the CI Pigment Yellow 101 is not given too much mechanical energy, and CI Pigment Yellow 101 having a high fluorescent color can be obtained even with a small diameter. In addition, the above range is preferable because there is little concern about contamination due to heat generation of the slurry and wear inside the mill. The peripheral speed of the stirring mechanism is preferably 6.0 m / s or more and 13.2 m / s or less, more preferably 7.2 m / s or more and 12.0 m / s or less, and even more preferably 8.4 m / s or more and 10.8 m / s or less.
[0051] The residence time in the mill may be freely set until the particle size is reduced to the desired size, but is preferably from 0.5 to 15 minutes, more preferably from 1 to 10 minutes, and even more preferably from 1.5 to 7.5 minutes.
[0052] -Bead mill operation method- The bead mill may be operated in a batch mode, a pass mode, or a circulation mode appropriately selected from these.
[0053] (post-process) After the diameter reduction, the slurry of CI Pigment Yellow 101 is taken out from the outlet of the container of the bead mill and dried. The drying may be natural drying or drying under reduced pressure.
[0054] By the above method, it is possible to produce CI Pigment Yellow 101, which has a small diameter but a high fluorescent color.
[0055] (Method of measuring the physical properties of CI Pigment Yellow 101) -Average particle size- The average particle size of CI Pigment Yellow 101 can be calculated as follows. The CI Pigment Yellow 101 after the reduction in diameter is observed and images are taken using a scanning electron microscope (SEM) (S-4100, manufactured by Hitachi, Ltd.), and the images are then imported into an image analyzer (LUZEXIII, manufactured by Nireco Corporation) for image analysis, whereby the amount of the pigment can be calculated. Specifically, the area of each particle is measured, and the equivalent circle diameter is calculated from this area value. The 50% diameter (D 50 ) is defined as the average particle size of CI Pigment Yellow 101. Image analysis is performed on 200 arbitrarily selected particles of CI Pigment Yellow 101.
[0056] -The diffraction angle 2θ of the peak in the X-ray diffraction pattern- The diffraction angle 2θ of a peak in an X-ray diffraction pattern obtained by powder X-ray diffraction method can be measured using an X-ray measuring device (Rigaku X-RAY DIFFRACTOMETER RINT-2100, manufactured by Rigaku Corporation). The measurement conditions are as follows. X-ray source:CuK α Sampling width: 0.02° Divergence slit: 1° Scattering slit: 1° Receiving slit: 0.3 mm Voltage: 30kV Current: 15mA Measurement range: 5.0° to 35.0° Step angle: 0.02° Step time: 1.2 seconds
[0057] <Coloring composition> The coloring composition of this embodiment contains CI Pigment Yellow 101 of this embodiment. The coloring composition according to the present embodiment is applied to an ink sheet for thermal transfer recording, a toner for developing an electrostatic image (specifically, toner particles), an ink for inkjet recording, a color filter, a writing pen, a colored plastic, other inks (paints, etc.), and the like. In particular, the composition according to this embodiment is preferably applied to a thermal transfer recording ink sheet, a toner, and an ink for inkjet recording.
[0058] Hereinafter, as a representative application, a toner for developing electrostatic images (specifically, toner particles) to which the composition according to this embodiment is applied will be described.
[0059] The toner for developing electrostatic images according to this embodiment (hereinafter also referred to as "toner") contains toner particles and, if necessary, an external additive.
[0060] (Toner particles) The toner particles contain, for example, a binder resin and the CI Pigment Yellow 101 of this embodiment. The toner particles may contain a colorant other than the CI Pigment Yellow 101 of this embodiment, a release agent, and other additives, as necessary.
[0061] Here, the content of CI Pigment Yellow 101 in this embodiment is preferably 3% by mass or more and 10% by mass or less, and more preferably 5% by mass or more and 8% by mass or less, based on the total mass of the toner particles.
[0062] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.
[0063] The binder resin is preferably a polyester resin. The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.
[0064] The "crystalline" nature of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.
[0065] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. The amorphous polyester resin may be a commercially available product or a synthesized product.
[0066] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0067] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0068] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0069] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0070] The amorphous polyester resin can be obtained by a known manufacturing method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.
[0071] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. The crystalline polyester resin may be a commercially available product or a synthesized product. Here, the crystalline polyester resin is preferably a polycondensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group, since the crystalline polyester resin can easily form a crystalline structure.
[0072] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polybasic carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0073] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0074] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.
[0075] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0076] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0077] The crystalline polyester resin can be obtained by a known manufacturing method, for example, in the same manner as the amorphous polyester.
[0078] The content of the binder resin is, for example, preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total amount of the toner particles.
[0079] -Coloring agent- The colorant includes CI Pigment Yellow 101 of this embodiment. Examples of colorants that may be used in combination with CI Pigment Yellow 101 of this embodiment include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, chalco oil blue, methyl methacrylate ... Examples of the pigment include various pigments such as methacrylate crosslinker, ... Specifically, the pigments are CI Pigment Yellow 1 (hereinafter, as they are all "CI Pigment Yellow", the description will be simplified and only the numbers will be listed), 3, 11, 12, 13, 14, 15, 16, 17, 20, 24, 31, 53, 55, 60, 61, 65, 71, 73, 74, 81, 83, 86, 93, 95, 97, and 98. , 99, 100, 104, 106, 108, 109, 110, 113, 114, 116, 117, 119, 120, 125, 126, 127, 128, 129, 137, 138, 139, 147, 148, 150, 151, 152, 153, 154, 155, 156, 166, 167, 168, 175, 180, 185; CI Pigment Orange 1 (hereafter, as these are all "CI Pigment Orange", we will simplify the description and list only the numbers), 5, 13, 14, 16, 17, 24, 34, 36, 38, 40, 43, 46, 49, 51, 55, 59, 61, 63, 64, 71, 73; CI Pigment Violet 1 (hereinafter, as these are all "CI Pigment Violet", we will simplify the description and list only the numbers), 19, 23, 29, 30, 32, 36, 37, 38, 39, 40, 50; CI Pigment Red 1 (hereinafter, as all of the above are "CI Pigment Red", we will simplify the description and list only the numbers), 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 40, 41, 42, 48:1, 48:2, 48:3, 48:4, 49:1, 49:2, 50:1, 52:1, 53:1, 57, 57:1, 57:2, 58:2, 58:4, 60:1, 63:1, 63:2, 64:1, 81:1, 83, 88, 90:1, 97, 101, 102, 10 4, 105, 106, 108, 112, 113, 114, 122, 123, 144, 146, 149, 150, 151, 155, 166, 168, 170, 171, 172, 174, 175, 176, 177, 178, 179, 180, 185, 187, 188, 190, 192, 193, 194, 202, 206, 207, 208, 209, 215, 216, 217, 220, 223, 224, 226, 227, 228, 238, 240, 242, 243, 245, 254, 255, 264, 265; CI Pigment Blue 1 (hereinafter, as these are all "CI Pigment Blues", we will simplify the description and only state the numbers), 2, 15, 15:3, 15:4, 15:6, 16, 22, 60, 64, 66, 76; CI Pigment Green 7, CI Pigment Green 36, CI Pigment Green 37, Pigment Green 58, CI Pigment Green 59; CI Pigment Brown 23, CI Pigment Brown 25, CI Pigment Brown 26, CI Pigment Brown 28; Examples include CI Pigment Black 1 and CI Pigment Black 7. The colorant may be used alone or in combination of two or more kinds.
[0080] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.
[0081] The content of the colorant is, for example, preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.
[0082] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.
[0083] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0084] The content of the release agent is, for example, preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total amount of the toner particles.
[0085] -Other additives- Examples of other additives include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.
[0086] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. Here, the toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.
[0087] The average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0088] The various average particle sizes and particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the average particle size D50v, the cumulative number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and number particle size D84p. Using these, the volumetric particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:
[0089] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0090] The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.
[0091] (External additives) Examples of the external additive include inorganic particles, such as SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2)n, Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, and MgSO4.
[0092] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the inorganic particles.
[0093] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).
[0094] The amount of the external additive added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0095] (Toner manufacturing method) Next, a method for producing the toner according to the present embodiment will be described. The toner according to the exemplary embodiment is obtained by producing toner particles and then externally adding an external additive to the toner particles.
[0096] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation-coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). The method for producing the toner particles is not particularly limited, and a well-known production method is adopted. Among these, it is preferable to obtain toner particles by the aggregation and coalescence method.
[0097] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, The toner particles are manufactured through a process of preparing a resin particle dispersion in which resin particles serving as a binder resin are dispersed, and a colorant particle dispersion in which a colorant (specifically, CI Pigment Yellow 101 in this embodiment) is dispersed (resin particle dispersion preparation process), a process of aggregating the resin particles and colorant particles (or other particles, if necessary) in a mixed dispersion of the resin particle dispersion and the colorant particle dispersion (or in a dispersion after mixing with other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation process), and a process of heating the aggregated particle dispersion in which the aggregated particles are dispersed, to fuse and coalesce the aggregated particles, thereby forming toner particles (fusion and coalescence process).
[0098] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a releasing agent will be described, but the releasing agent is used as necessary. Of course, additives other than the releasing agent may be used.
[0099] -Resin particle dispersion preparation process- First, a resin particle dispersion in which resin particles serving as a binder resin are dispersed, as well as a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared.
[0100] Here, the resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.
[0101] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more.
[0102] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0103] In the resin particle dispersion, examples of the method for dispersing the resin particles in the dispersion medium include general dispersion methods using, for example, a rotary shear type homogenizer, a ball mill having a media, a sand mill, a dyno mill, etc. Depending on the type of resin particles, the resin particles may be dispersed in the resin particle dispersion using, for example, a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to effect conversion of the resin from W / O to O / W (so-called phase inversion), resulting in a discontinuous phase, and the resin is dispersed in particulate form in the aqueous medium.
[0104] The average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the average particle size D50v. The average particle sizes of particles in other dispersions are also measured in the same manner.
[0105] The content of the resin particles in the resin particle dispersion is, for example, preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0106] In addition, for example, a colorant particle dispersion and a release agent particle dispersion are also prepared in the same manner as the resin particle dispersion. That is, the average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0107] -Agglomerated particle formation process- Next, the colorant particle dispersion and the release agent particle dispersion are mixed together with the resin particle dispersion. Then, in the mixed dispersion, the resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.
[0108] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature of the glass transition temperature of the resin particles (specifically, for example, a temperature of the glass transition temperature of the resin particles -30°C or more and the glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the above-mentioned aggregating agent may be added to the mixed dispersion at room temperature (e.g., 25°C) while stirring the mixed dispersion with a rotary shear homogenizer, the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), and a dispersion stabilizer may be added as necessary, followed by the above-mentioned heating.
[0109] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant used as the dispersant added to the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. In particular, when a metal complex is used as the flocculant, the amount of surfactant used is reduced and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ions of the flocculant may be used, and a chelating agent is preferably used as this additive.
[0110] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0111] -Fusion / unification process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10 to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles, thereby forming toner particles.
[0112] Through the above steps, toner particles are obtained. Note that, after obtaining an aggregated particle dispersion liquid in which aggregated particles are dispersed, the toner particles may be manufactured through a process of further mixing the aggregated particle dispersion liquid with a resin particle dispersion liquid in which resin particles are dispersed, and aggregating the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles to form second aggregated particles, and a process of heating the second aggregated particle dispersion liquid in which the second aggregated particles are dispersed to fuse and coalesce the second aggregated particles to form toner particles having a core / shell structure.
[0113] After the fusion and coalescence process, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain toner particles in a dried state. In the washing step, it is preferable to carry out sufficient replacement washing with ion-exchanged water from the viewpoint of electrostatic charge. In addition, the solid-liquid separation step is not particularly limited, but it is preferable to carry out suction filtration, pressure filtration, etc. from the viewpoint of productivity. In addition, in the drying step, there is no particular limit to the method, but it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc. from the viewpoint of productivity.
[0114] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0115] <Electrostatic image developer> The electrostatic image developer according to this embodiment contains at least the toner according to this embodiment. The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner according to the present embodiment, or may be a two-component developer in which the toner is mixed with a carrier.
[0116] The carrier is not particularly limited, and may be any known carrier, such as a coated carrier in which the surface of a core material made of magnetic powder is coated with a coating resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, or a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material and are coated with a coating resin.
[0117] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.
[0118] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing an organosiloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, and epoxy resin. The coating resin and the matrix resin may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0119] Here, in order to coat the surface of the core material with a coating resin, a method of coating with a coating layer forming solution in which the coating resin and, if necessary, various additives are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the coating resin to be used, the suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer, a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material, a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air, and a kneader coater method in which the core material of a carrier and the solution for forming a coating layer are mixed in a kneader coater and the solvent is removed.
[0120] In the two-component developer, the mixture ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100. EXAMPLES
[0121] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples in any way.
[0122] <Example 1> CI Pigment Yellow 101 (manufactured by BASF, average particle size: 3 μm) was made smaller in size as follows. In the pre-process, CI Pigment Yellow 101 was wetted with water containing 5% by mass of a surfactant (Teika Power BN2060, manufactured by Teika Corporation) relative to the CI Pigment Yellow 101 to prepare a slurry with a solid concentration of 20%. In the diameter reduction process, a continuous key mill (KMC-3, manufactured by Inoue Seisakusho Co., Ltd.) was used. The conditions were as follows: high-purity alumina beads (TB-01 manufactured by Taimei Chemical Industry Co., Ltd.) with a specific gravity of 3.9 and a diameter of 0.10 mm were used; the bead filling rate was set to 80% of the volume of the bead mill container; the peripheral speed of the stirring mechanism was set to 9.3 m / s; and the diameter reduction was continued until the average particle size reached 700 nm. After diameter reduction was completed, the slurry was dried under reduced pressure to obtain powdered CI Pigment Yellow 101, which was then measured and evaluated.
[0123] <Example 2> The particles were reduced in size in the same manner as in Example 1, except that the average particle size after reduction was set to 500 nm.
[0124] <Example 3> The particles were reduced in size in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm.
[0125] <Example 4> The particles were reduced in size in the same manner as in Example 1, except that the average particle size after reduction was set to 150 nm.
[0126] <Example 5> The particles were reduced in size in the same manner as in Example 1, except that the average particle size after reduction was set to 100 nm.
[0127] <Example 6> The diameter was reduced in the same manner as in Example 1, except that the beads used were glass beads (BZ-01, manufactured by AS ONE Corporation) with a specific gravity of 2.5 and a diameter of 0.10 mm.
[0128] <Example 7> The diameter was reduced in the same manner as in Example 1, except that the beads used were zirconia beads (YTZ-0.1 manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.10 mm.
[0129] <Example 8> Except for using stainless steel beads with a specific gravity of 7.6 and a bead diameter of 0.11 mm, the diameter was reduced in the same manner as in Example 1. The stainless steel beads with an average bead diameter of 0.11 mm were SUS304-150 manufactured by Fuji Manufacturing Co., Ltd., with a bead diameter of 125 to 45 μm, and were used after removing beads with a diameter of 90 μm or less with a 90 μm sieve.
[0130] <Example 9> The beads were reduced in diameter in the same manner as in Example 1, except that the beads used were zirconia beads (YTZ-0.03, manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.03 mm, and the bead mill device was an Easy Nano RMB type (manufactured by Imex Co., Ltd.).
[0131] <Example 10> The diameter of the beads was reduced in the same manner as in Example 1, except that the beads used were high-purity alumina beads (TB-03, manufactured by Taimei Chemical Industry Co., Ltd.) with a specific gravity of 3.9 and a bead diameter of 0.30 mm.
[0132] <Example 11> The diameter of the beads was reduced in the same manner as in Example 1, except that the beads used were high-purity alumina beads having a specific gravity of 3.9 and a bead diameter of 0.40 mm (TB-04 manufactured by Taimei Chemical Industry Co., Ltd.).
[0133] <Example 12> The diameter was reduced in the same manner as in Example 1, except that the peripheral speed of the stirring mechanism was set to 4.8 m / s.
[0134] <Example 13> The diameter was reduced in the same manner as in Example 1, except that the peripheral speed of the stirring mechanism was set to 14.4 m / s.
[0135] <Example 14> The diameter was reduced in the same manner as in Example 1, except that the bead mill device was an Easy Nano RMB type (manufactured by Imex Co., Ltd.) and the peripheral speed of the stirring mechanism was 15.0 m / s.
[0136] <Example 15> The beads were reduced in diameter in the same manner as in Example 1, except that the beads used were zirconia beads (YTZ-0.3 manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.30 mm, and the peripheral speed of the stirring mechanism was 14.4 m / s.
[0137] <Example 16> The diameter was reduced in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the beads used were glass beads (BZ-01, manufactured by AS ONE Corporation) with a specific gravity of 2.5 and a bead diameter of 0.10 mm.
[0138] <Example 17> The diameter was reduced in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the beads used were zirconia beads (YTZ-0.1 manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.10 mm.
[0139] <Example 18> The diameter was reduced in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm, the beads used were zirconia beads (YTZ-0.03, manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.03 mm, and the bead mill device was an Easy Nano RMB type (manufactured by IMEX Co., Ltd.).
[0140] <Example 19> The diameter was reduced in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the beads used were high-purity alumina beads (TB-03 manufactured by Taimei Chemical Industry Co., Ltd.) with a specific gravity of 3.9 and a bead diameter of 0.30 mm.
[0141] <Example 20> The particles were reduced in diameter in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the peripheral speed of the stirring mechanism was set to 4.8 m / s.
[0142] <Example 21> The particles were reduced in diameter in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the peripheral speed of the stirring mechanism was set to 14.4 m / s.
[0143] <Example 22> The diameter was reduced in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm, the beads used were zirconia beads (YTZ-0.3 manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.30 mm, and the peripheral speed of the stirring mechanism was set to 14.4 m / s.
[0144] <Example 23> The beads were reduced in diameter in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the bead packing rate was set to 70%.
[0145] <Example 24> The beads were reduced in diameter in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the bead packing rate was set to 90%.
[0146] <Example 25> The particle size was reduced in the same manner as in Example 1, except that the CI Pigment Yellow 101 used was from a different production lot manufactured by BASF (average particle size: 5 μm) and the average particle size after reduction was 250 nm.
[0147] <Example 26> The particle size was reduced in the same manner as in Example 1, except that the CI Pigment Yellow 101 used was manufactured by Neelicon (average particle size: 1 μm) and the average particle size after reduction was set to 250 nm.
[0148] <Comparative Example 1> The particle size reduction method was high-pressure dispersion, and the particle size reduction was carried out using an impact type disperser, Ultimizer (manufactured by Sugino Machine Co., Ltd.) The slurry was prepared in the same manner as in Example 1, and the particles were reduced in size under a pressure of 240 MPa until the average particle size became 700 nm.
[0149] <Comparative Example 2> The beads were reduced in diameter in the same manner as in Example 1, except that the beads used were zirconia beads (YTZ-0.4 manufactured by Nikkato Corporation) with a specific gravity of 6.0 and a bead diameter of 0.40 mm, the bead mill device was an Easy Nano RMB type (manufactured by IMEX Co., Ltd.), and the peripheral speed of the stirring mechanism was 15.0 m / s.
[0150] <Comparative Example 3> Except for setting the average particle size after reduction to 250 nm and using stainless steel beads with a specific gravity of 7.6 and a bead diameter of 0.11 mm, the beads were reduced in diameter in the same manner as in Example 1. The stainless steel beads with an average bead diameter of 0.11 mm were SUS304-150 manufactured by Fuji Manufacturing Co., Ltd. with a bead diameter of 125 to 45 μm, which were sieved with a 90 μm sieve to remove beads with a diameter of 90 μm or less.
[0151] <Comparative Example 4> The diameter was reduced in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm and the beads used were high-purity alumina beads (TB-04 manufactured by Taimei Chemical Industry Co., Ltd.) with a specific gravity of 3.9 and a bead diameter of 0.40 mm.
[0152] <Comparative Example 5> The beads were reduced in diameter in the same manner as in Example 1, except that the average particle size after reduction was set to 250 nm, the bead mill device was an Easy Nano RMB type (manufactured by Imex Co., Ltd.), and the peripheral speed of the stirring mechanism was set to 15.0 m / s.
[0153] <Measurement> The following physical properties of the CI Pigment Yellow 101 (after drying) obtained in the examples and comparative examples after particle size reduction were measured according to the methods described above. ·Average particle size · Diffraction angle 2θ of a peak in an X-ray diffraction pattern
[0154] <Evaluation> The spectral reflectance at 520 nm of the CI Pigment Yellow 101 after the reduction in size (after drying) was measured using a spectrophotometer eXact (registered trademark) (manufactured by X-rite). Next, the fluorescent color of the CI Pigment Yellow 101 after the reduction in size was evaluated based on the spectral reflectance. The evaluation was performed according to the following criteria.
[0155] A: 110 or more B: 90 or more C: Less than 90
[0156] The results are shown in Table 1.
[0157] [Table 1-1]
[0158] [Table 1-2]
[0159] The results in Table 1 show that in this embodiment, CI Pigment Yellow 101 having a high fluorescent color can be obtained even with a small diameter, as compared with the comparative example. As an example, FIG. 1 shows X-ray diffraction patterns obtained by powder X-ray diffraction of CI Pigment Yellow 101 before size reduction (see FIG. 1(A)), CI Pigment Yellow 101 of the embodiment after size reduction (see FIG. 1(B)), and CI Pigment Yellow 101 of the comparative example after size reduction (see FIG. 1(C)). As shown in FIG. 1, it can be seen that the peaks in the X-ray diffraction pattern of CI Pigment Yellow 101 of the embodiment after size reduction (see FIG. 1(B)) are not excessively shifted from those of CI Pigment Yellow 101 before size reduction (see FIG. 1(A)), as is the case with CI Pigment Yellow 101 of the comparative example after size reduction (see FIG. 1(C)). As a result, in this embodiment, CI Pigment Yellow 101 having a high fluorescent color even with a small diameter is obtained as compared to the comparative example.
[0160] <Examples 101 to 126> The toners and developers using CI Pigment Yellow 101 in Examples 1 to 26 were prepared by the following procedure.
[0161] -Preparation of CI Pigment Yellow 101 Dispersion- In the particle size reduction step in Examples 1 to 26, a CI Pigment Yellow 101 dispersion having a solid content of 20 mass % was obtained from the CI Pigment Yellow 101 dispersion after particle size reduction and before drying.
[0162] -Preparation of resin particle dispersion- Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 mole parts Bisphenol A propylene oxide adduct: 95 parts by mole The above materials were charged into a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 220°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued at that temperature for 1 hour, after which the reactant was cooled. Thus, a polyester resin with a weight average molecular weight of 18,000 and a glass transition temperature of 60°C was obtained. In a vessel equipped with a temperature control means and a nitrogen substitution means, 40 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of polyester resin were gradually added and dissolved therein, and a 10% by mass aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was dropped at a rate of 2 parts / min while stirring the mixed liquid. After the dropping was completed, the temperature was returned to room temperature (20°C to 25°C), and bubbling with dry nitrogen was performed for 48 hours while stirring to obtain a resin particle dispersion in which ethyl acetate and 2-butanol were reduced to 1,000 ppm or less. Ion-exchanged water was added to the resin particle dispersion to adjust the solid content to 20% by mass, and a resin particle dispersion was obtained.
[0163] -Preparation of release agent particle dispersion- Paraffin wax (HNP-9, manufactured by Nippon Seiro Co., Ltd.): 100 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (IKA, product name Ultra Turrax T50), and then dispersed using a Manton-Gaulin high-pressure homogenizer (Gaulin) to obtain a release agent particle dispersion (solid content 20% by mass) in which release agent particles having a volume average particle size of 200 nm were dispersed.
[0164] -Production of toner particles- ·Resin particle dispersion: 400 parts CI Pigment Yellow 101 Dispersion: 50 parts Release agent particle dispersion: 25 parts Anionic surfactant (Daiichi Kogyo Seiyaku Co., Ltd.: Neogen RK, 20%): 10 parts The above materials were placed in a round stainless steel flask, and 0.1N (=mol / L) nitric acid was added to adjust the pH to 3.5, and then 30 parts of a nitric acid aqueous solution with a polyaluminum chloride concentration of 10% by mass was added. Next, the mixture was dispersed at a liquid temperature of 30°C using a homogenizer (IKA, product name Ultra Turrax T50), and then heated to 45°C in a heating oil bath and held for 30 minutes. Then, 50 parts of the resin particle dispersion was added and held for 1 hour, and 0.1N sodium hydroxide aqueous solution was added to adjust the pH to 8.5, and then heated to 84°C and held for 2.5 hours. Next, the mixture was cooled to 20°C at a rate of 20°C / min, and the solid content was filtered off, thoroughly washed with ion-exchanged water, and dried to obtain toner particles. The volume average particle size of the toner particles was 5.8 μm.
[0165] -Creating the carrier- Ferrite particles (average particle size 35 μm): 100 parts Toluene: 14 parts Polymethyl methacrylate (MMA, weight average molecular weight 75,000): 5 parts Carbon black: 0.2 parts (VXC-72, manufactured by Cabot Corporation, volume resistivity: 100 Ω cm or less) The above materials except for the ferrite particles were dispersed in a sand mill to prepare a dispersion liquid, and this dispersion liquid was placed in a vacuum degassing kneader together with the ferrite particles, and the mixture was dried under reduced pressure while stirring to obtain a carrier.
[0166] - Toner production - 100 parts of the obtained toner particles were mixed and blended with 1.5 parts of hydrophobic silica (manufactured by Nippon Aerosil Co., Ltd., RY50) and 1.0 part of hydrophobic titanium oxide (manufactured by Nippon Aerosil Co., Ltd., T805) using a sample mill at 10,000 rpm (revolutions per minute) for 30 seconds. The mixture was then sieved using a vibrating sieve with 45 μm openings to prepare a toner. The volume average particle size of the obtained toner was 5.8 μm.
[0167] -Preparation of electrostatic image developer- Eight parts of the toner and 92 parts of the carrier were mixed in a V blender to prepare an electrostatic image developer.
[0168] <Evaluation (Color Development)> When the resulting developers of each example were evaluated, all of them showed excellent color development.
[0169] The present embodiment includes the following aspects. (((1))) The average particle size is 100 nm or more and 700 nm or less, In the X-ray diffraction pattern obtained by powder X-ray diffraction method, the second peak from the low angle side is present in the range of diffraction angle 2θ = 11.66 ° or more and 11.86 ° or less. CI Pigment Yellow 101. (((2))) CI Pigment Yellow 101 as described in (((1))) having an average particle size of 150 nm or more and 500 nm or less. (((3))) CI Pigment Yellow 101 according to (((1))) or (((2))), in which the third peak from the low angle side is present in the range of diffraction angle 2θ = 17.86° or more and 18.06° or less in an X-ray diffraction pattern obtained by powder X-ray diffraction method. (((4))) A method for producing CI Pigment Yellow 101 according to any one of (((1))) to (((3))), comprising reducing the diameter of CI Pigment Yellow 101 having an average particle size of 1 μm or more and 5 μm or less, using beads having a specific gravity of 2.5 to 6.0 and a bead diameter of 0.03 mm to 0.3 mm, under conditions of a peripheral speed of a stirring mechanism of 4.8 m / s to 14.4 m / s. (((5))) A coloring composition comprising CI Pigment Yellow 101 according to any one of (((1))) to (((3))). (((6))) The coloring composition according to (((5))), which is a toner for developing an electrostatic image.
[0170] The advantages of the above aspect are as follows. According to the invention of (((1))), there is provided CI Pigment Yellow 101 which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in a range of diffraction angles 2θ=11.66° or more or 2θ=11.86° or more, and which has a higher fluorescent color even though it has a smaller particle size than CI Pigment Yellow 101.
[0171] According to the invention related to (((2))), CI Pigment Yellow 101 is provided that has a high fluorescent color even with a small diameter, compared to when the average particle size is 100 nm or more but less than 150 nm, or more than 500 nm but not more than 700 nm.
[0172] According to the invention related to (((3))), there is provided CI Pigment Yellow 101 which has a high fluorescent color even with a small diameter, as compared with a case in which, in an X-ray diffraction pattern obtained by powder X-ray diffraction, the second peak from the low-angle side is in the range of diffraction angles 2θ=11.66° or more and 11.86° or less, and, in an X-ray diffraction pattern obtained by powder X-ray diffraction, the third peak from the low-angle side is in the range of diffraction angles 2θ=less than 17.86° or more than 2θ=18.06°.
[0173] According to the invention related to (((4))), there is provided a method for producing CI Pigment Yellow 101 having a high fluorescent color even with a small diameter, as compared with a method for producing CI Pigment Yellow 101 that includes reducing the diameter of CI Pigment Yellow 101 having an average particle diameter of 1 μm or more and 5 μm or less under conditions in which beads having a specific gravity of less than 2.5 or more than 6.0, or a bead diameter of less than 0.03 mm or more than 0.3 mm, are used, or the peripheral speed of the stirring mechanism is less than 4.8 m / s or more than 14.4 m / s.
[0174] According to the invention related to (((5))), there is provided a coloring composition containing CI Pigment Yellow 101 which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low angle side is present in a diffraction angle range of less than 2θ=11.66° or more than 2θ=11.86°, and which has a high fluorescent color even with a small particle size compared to the case where CI Pigment Yellow 101 is used.
[0175] According to the invention related to (((6))), there is provided a coloring composition, which is a toner for developing electrostatic images, containing CI Pigment Yellow 101, which has an average particle size of 100 nm or more and 700 nm or less, and in an X-ray diffraction pattern obtained by a powder X-ray diffraction method, the second peak from the low-angle side is present in a range of diffraction angles 2θ=11.66° or more or 2θ=11.86° or more, and has a high fluorescent color even with a small particle size compared to when CI Pigment Yellow 101 is used.
Claims
1. having an average particle size of 100 nm or more and 700 nm or less; In the X-ray diffraction pattern obtained by powder X-ray diffraction method, the second peak from the low angle side is present in the range of diffraction angle 2θ = 11.66 ° or more and 11.86 ° or less. C.I. Pigment Yellow 101.
2. 2. The C.I. Pigment Yellow 101 of claim 1, having an average particle size of 150 nm or more and 500 nm or less.
3. 2. C.I. Pigment Yellow 101 according to claim 1, wherein the third peak from the low angle side is in the range of a diffraction angle 2θ of 17.86° or more and 18.06° or less in an X-ray diffraction pattern obtained by a powder X-ray diffraction method.
4. The method for producing C.I. Pigment Yellow 101 according to claim 1, comprising reducing the diameter of C.I. Pigment Yellow 101 having an average particle size of 1 μm to 5 μm under the condition of a peripheral speed of a stirring mechanism of 4.8 m / s to 14.4 m / s using beads having a specific gravity of 2.5 to 6.0 and a bead diameter of 0.03 mm to 0.3 mm.
5. A coloring composition comprising the C. I. Pigment Yellow 101 according to any one of claims 1 to 3.
6. The coloring composition according to claim 5 , which is a toner for developing electrostatic images.
Citation Information
Patent Citations
Insoluble azo pigment and colored composition
JP2004026930A